1998
DOI: 10.1073/pnas.95.14.7866
|View full text |Cite
|
Sign up to set email alerts
|

An adenoviral vector deleted for all viral coding sequences results in enhanced safety and extended expression of a leptin transgene

Abstract: Adenoviral (Ad)-mediated in vivo gene transfer and expression are limited in part by cellular immune responses to viral-encoded proteins and͞or transgene immunogenicity. In an attempt to diminish the former responses, we have previously developed and described helper-dependent (HD) Ad vectors in which the viral protein coding sequences are completely eliminated. These HD vectors have up to 37 kb insert capacity, are easily propagated in a Cre recombinasebased system, and can be produced to high concentration a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
237
1
1

Year Published

1999
1999
2006
2006

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 357 publications
(247 citation statements)
references
References 35 publications
8
237
1
1
Order By: Relevance
“…Some researchers have reported that immune reaction to rAd has been suppressed by FK506 immunosuppression agent, 7 CTLA4Ig, 8 and a gutted adenovirus vector. [9][10][11] Thus, repetitive transduction to skeletal muscle could seem valid for consecutive expression of a therapeutic gene. The latter is caused by a maturation-dependent loss of the myofiber's susceptibility to rAd uptake which is due to structural and biochemical changes during muscle maturation.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have reported that immune reaction to rAd has been suppressed by FK506 immunosuppression agent, 7 CTLA4Ig, 8 and a gutted adenovirus vector. [9][10][11] Thus, repetitive transduction to skeletal muscle could seem valid for consecutive expression of a therapeutic gene. The latter is caused by a maturation-dependent loss of the myofiber's susceptibility to rAd uptake which is due to structural and biochemical changes during muscle maturation.…”
Section: Introductionmentioning
confidence: 99%
“…11,14 -16 In addition, the elimination of all the adenoviral genes leaves room to allocate large expression cassettes, and therefore gutless adenoviruses are also designed as high-capacity adenoviral vectors. 11,14 -16 For correction of metabolic and/or hereditary diseases, different authors have used gutless vectors with nonregulable promoters showing long-term expression of transgenes such as ␣1-antitrypsin, 17,18 leptin, 19 apolipoprotein E, 20 and factor VIII and IX [21][22][23][24] at therapeutic levels without apparent hepatic toxicity.…”
mentioning
confidence: 99%
“…41,62,63 Last-generation helper-dependent or Gutless adenovirus R Alba et al gutless adenovirus vectors display reduced long-term toxicity and prolonged transgene expression compared to first-generation vectors after administration to peripheral organs of immunologically naïve animals. 56,[64][65][66][67][68] Lack of coding viral genes may account for reduced adaptive cellular immune response after systemic delivery of gutless vectors. Initially, gutless vectors are capable of transducing dendritic cells and stimulating Ad-specific T-cell responses, independent of viral gene transcription.…”
Section: Gutless Adenovirus and Immune Responsementioning
confidence: 99%
“…68 Gutless vectors have been shown to express non-immunogenic transgenes during the whole life of the mouse, while expression driven by first-generation adenovirus lasted at most for 3 months. [80][81][82] Therapeutic genes carried by gutless vectors have been administered to the liver of mouse models for different diseases, such as hemophilia A and B, 83,84 obesity, 66 familial hypercholesterolemia, 81,85-87 ornithine transcarbamylase deficiency, 88 diabetes 89 and chronic viral hepatitis. 90,91 Therapeutic levels of most proteins have been documented for a long-term duration.…”
Section: Gutless Adenovirus and Immune Responsementioning
confidence: 99%